Asset Liquidity in Monetary Theory and Finance: A Unified Approach - Athanasios Geromichalos; Kuk Mo Jung; Seungduck Lee; Dillon Carlos (University of California, Department of Economics, 2019)
Economists often say that certain types of assets, e.g., Treasury bonds, are very 'liquid'. Do they mean that these assets are likely to serve as media of exchange or collateral (a definition of liquidity often employed in monetary theory), or that they can be easily sold in a secondary market, if needed (a definition of liquidity closer to the one adopted in finance)? We develop a model where these two notions of asset liquidity coexist, and their relative importance is determined endogenously in general equilibrium: how likely agents are to visit a secondary market in order to sell assets for money depends on whether sellers of goods/services accept these assets as means of payment. But, also, the incentive of sellers to invest in a technology that allows them to recognize and accept assets as means of payment depends on the existence (and efficiency) of a secondary market where buyers could liquidate assets for cash. The interaction between these two channels offers new insights regarding the determination of asset prices and the ability of assets to facilitate transactions and improve welfare.
Keywords: E40; E50; G11; G12; G14; 330; Information; Over-the-Counter Markets; Search and Matching; Liquidity; Asset prices; Monetary policy